2022
DOI: 10.1097/md.0000000000030263
|View full text |Cite
|
Sign up to set email alerts
|

The association between vitamin D levels and heart rate variability in patients with type 2 diabetes mellitus

Abstract: To assess the association between serum vitamin D levels and heart rate variability in patients with type 2 diabetes mellitus (T2DM). This study included 469 patients who were retrospective assessed for eligibility from Changzhou Second People’s Hospital, Affiliated Nanjing Medical University, between March 2013 and June 2020. A total of 191 T2DM patients were recruited and divided into 3 groups. A total of 191 patients were recruited. A significant difference was noted among groups for HbA1c (P < .001), serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This is supported by Li Ye Chen and et.al., who found that vitamin D deficiency is associated with a lower SDNN compared to that of the sufficient group. The reason may be that vitamin D deficiency is associated with a decrease in the functions of the parasympathetic system [56]. Moreover, Canpolat et.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Li Ye Chen and et.al., who found that vitamin D deficiency is associated with a lower SDNN compared to that of the sufficient group. The reason may be that vitamin D deficiency is associated with a decrease in the functions of the parasympathetic system [56]. Moreover, Canpolat et.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Li Ye Chen et al, who found that vitamin D deficiency is associated with a lower SDNN compared to that of the sufficient group. The reason may be that vitamin D deficiency is associated with a decrease in the functions of the parasympathetic system [ 56 ]. Canpolat et al’s studies have shown that autonomic function of the heart can be impaired in the absence of heart damage and symptoms in people with vitamin D deficiency [ 57 ].…”
Section: Discussionmentioning
confidence: 99%